Calcium and Vitamin D in the Regulation of Energy Balance: Where do we Stand? - Soares, Mario; Pathak, K.; Calton, Emily (MDPIAG, 2014)
There is a pandemic of obesity and associated chronic diseases. Dietary calcium and vitamin D have many extra-skeletal roles in human health. In this review we have summarized the current understanding of their influence on human energy balance by examining the epidemiological, clinical, animal, cellular and molecular evidence. We opine that while calcium and vitamin D are functional nutrients in the battle against obesity, there is a need for prospective human trials to tilt the balance of evidence in favour of these nutrients.